THE PRINCIPAL’S MANAGEMENT IN PREVENTING BULLYING THROUGH THE CHILD-FRIENDLY SCHOOL PROGRAM AT SMP NEGERI 6 SANGATTA UTARA - Herpina Martangi Sianturi; Widyatmike Gede Mulawarman; Haeruddin; Khusnul Khotimah; Laili Komariyah; Nurlaili (RADJA PUBLIKA, 2026)
This study aimed to analyze the principal's management in preventing bullying behavior through the Child-Friendly School Program at SMP Negeri 6 Sangatta Utara. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, involving the principal, vice principal, teachers, educational staff, students, and parents as informants. The data were analyzed using the interactive model of Miles and Huberman, which includes data collection, data reduction, data display, and conclusion drawing or verification. The findings revealed that the principal's management in bullying prevention was implemented through four management functions, namely planning, organizing, actuating, and controlling or evaluating. In the planning aspect, anti-bullying policies were systematically, participatively, and integratively incorporated into official school documents. In the organizing aspect, the principal established a clear work structure involving various school stakeholders. In the implementation aspect, bullying prevention was carried out through preventive, educative, and corrective approaches, including socialization, character building, counseling services, and gradual case handling. In the controlling and evaluation aspect, the principal conducts continuous monitoring, coordination, and follow-up actions to improve program effectiveness. This study concludes that the success of bullying prevention depends not only on the existence of formal policies but also on the principal's managerial capacity to implement the Child-Friendly School Program consistently, collaboratively, humanely, and with a strong orientation toward child protection